2015
DOI: 10.1371/journal.pone.0128592
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Characterization of Cymbidium sinense 'Dharma' Using 454 Pyrosequencing and Its Application in the Identification of Genes Associated with Leaf Color Variation

Abstract: The highly variable leaf color of Cymbidium sinense significantly improves its horticultural and economic value, and makes it highly desirable in the flower markets in China and Southeast Asia. However, little is understood about the molecular mechanism underlying leaf-color variations. In this study, we found the content of photosynthetic pigments, especially chlorophyll degradation metabolite in the leaf-color mutants is distinguished significantly from that in the wild type of Cymbidium sinense 'Dharma'. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…The regulation of plant leaf color is a complex process. Most of the previous studies analyzed the mechanism of leaf color formation by methods of physiology, cytology and molecular biology [1], but the mechanism of leaf color regulation from the perspective of small molecular metabolites needs to be studied further. In this study, based on UPLC-MS/MS, the changes of metabolites in the process of leaf color change of C. sinense 'Red Sun' were qualitatively and quantitatively analyzed, and the unique pattern of flavonoid-related metabolites in the process of leaf color change was constructed for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The regulation of plant leaf color is a complex process. Most of the previous studies analyzed the mechanism of leaf color formation by methods of physiology, cytology and molecular biology [1], but the mechanism of leaf color regulation from the perspective of small molecular metabolites needs to be studied further. In this study, based on UPLC-MS/MS, the changes of metabolites in the process of leaf color change of C. sinense 'Red Sun' were qualitatively and quantitatively analyzed, and the unique pattern of flavonoid-related metabolites in the process of leaf color change was constructed for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The most important phenotypic feature of C. sinense is that it has a very rich variation in leaf color, which improves its ornamental and economic values. C. sinense contains a number of varieties based on the location and color of leaf variegation, including chimera art, claw art, crown art, crane art, middle penetration art, spot art and treasure art and so on [1]. At present, the leaf variegation varieties of C. sinense are basically yellow-green leaves, but there are few reports about red leaves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the data were normalized against the expression of reference gene ACTIN, as previously described 44 . The transcript levels for these genes were summarized from three replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on leaf color mutant of Cymbidium sinense 'Dharma' have demonstrated that the gene encoding key enzyme of chlorophyll degradation is expressed at a higher level, which is consistent with its lower chlorophyll content. It suggests that leaf color variation may be due to the excessive degradation of chlorophyll [16]. In addition, the upregulated expression of genes involved in flavonoid biosynthesis and the downregulation of genes involved in carotenoid biosynthesis may be related to the yellow-leaf phenotype [17].…”
Section: Introductionmentioning
confidence: 99%